Assessment of Environmental Radioactivity and Radiation for Human Health Risk - Tokonami, Shinji; Kashiwakura, Ikuo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Ten years have passed since the nuclear accident occurred in Fukushima, Japan, following the Great East Japan earthquake. Thereafter, many people around the world have been concerned about the risks posed by radiation. They still believe that even a small amount of radiation exposure will affect human health. In reality, however, there are many natural radionuclides in the environment, which emit a variety of types of radiation. Although it is well known that there is a positively linear relationship between acute radiation exposure and cancer risk in atomic bomb survivors, the risk of chronic radiation exposure due to natural radionuclides cannot be well explained to people who have lived in high-background radiation areas for many generations. Therefore, more studies in this research field are required to obtain new scientific findings. In order to promote further scientific activities, it will be the best for us to understand the current status of this field by summarizing what we have apprehended so far. This Special Issue will highlight measurement data, methodologies, radiation biology, and risk assessment related to radiation.